TINJAUAN KRIMINOLOGI DALAM CYBERBULLYING TERHADAP ANAK (STUDI KASUS DI MTSS PELITA GEDONG TATAAN) - Nurlis Effendi (Universitas Bandar Lampung (UBL), 2021)
KPAI released the results of monitoring cases of violations of children's rights in the field of education from January to April 2019 where the trend of cases wasdominated by bullying and physical violence. These data are sourced from the KPAIcomplaint division, both direct complaints and online complaints. KPAI Commissionerfor Education, Retno Listyarti said that violations of children's rights in the field ofeducation are still dominated by bullying, namely physical violence, psychological violence, and sexual violence. In addition, child victims of the policy are also quite high in cases. based on education level, the majority of cases occurred at theelementary/equivalent level, namely as many as 25 cases or reaching 67 percent, thejunior high level equivalent as many as 5 cases, high school level equivalent as many as6 cases and higher education (PT) as many as 1 case. The results showed that 35.8% ofstudents had experienced or were victims of bullying that had not been specifiedwhether it was physical bullying, verbal bullying, relational bullying and electronicbullying. And do not know whether students experience the effects of bullying such aslowering a child's motivation to go to school, hindering achievement, increasing childaggressiveness, and causing depression. One of the factors that encourage perpetratorsto commit cyber bullying is that the perpetrators do not understand the function ofsocial media and do not know that there are rules that must be obeyed by social mediausers so as not to harm others. Young people do not understand the laws andregulations governing certain criminal acts, in this case the ITE Law Number 11 of2008 that hate speech, insults, and others are offenses that can be punished.